THE EFFECT OF ENVIRONMENTAL PERFORMANCE ON PROFITABILITY COMPANIES: STUDY ON INDEXED COMPANIES SRI-KEHATI - Najia; Wardhiah; Marzuki; Rico Nur Ilham (RADJA PUBLIKA, 2025)
This research aims to determine the effect of environmental performance on company profitability. The type of research used is quantitative research with secondary data types. The data source in this research is financial report data. The data collection technique used is documentation analysis technique. The data analysis technique used in this research is panel data analysis. The population in this study were all 25 companies listed on the Sri-Kehati index using a saturated sampling method. Research sample with a total of 75 observations. The research results show that partially environmental performance, ISO 1401 and environmental costs have a positive and significant effect on company profitability.